Oral preventive medications for migraine in adults aged 18–65: a network meta-analysis - Wu, Jianping; Wu, Jun; Zhang, Jian; Liu, Bingbing; Song, Xinyuan; Wu, Yuanjie; Tian, Fanian; Ding, Yanbing; Wang, Ping (Frontiers in Pharmacology, 2025)
BackgroundMigraine is a highly prevalent neurological disorder that significantly impairs quality of life. Understanding the comparative effectiveness and safety of oral preventive medications is essential to guide treatment decisions in adult patients. This study aims to evaluate and compare the efficacy and safety of oral pharmacological therapies for migraine prevention in adults using Network Meta-Analysis.MethodsA comprehensive search was conducted across The Cochrane Library, PubMed, SCOPUS, and Embase databases until 15 December 2024 to find relevant studies on preventing migraine among adult populations. Clinical trials involving adult individuals with migraine who received oral pharmacological interventions were included. Per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, data extraction was independently conducted by five researchers in duplicate. Model choice was based on heterogeneity with random-effects used for I2 ≥ 50% and fixed-effects for I2 < 50%. The main endpoint was the monthly frequency of migraine attacks. Secondary endpoints encompassed the response rate of ≥50%, migraine duration, pain intensity, and quality of life (QoL). Adverse events were assessed.ResultsFrom the 17,443 identified citations, we included 44 trials (4,612 participants) in our analysis. Topiramate, valproate, and propranolol demonstrated significant efficacy in the prevention of migraines. Memantine, melatonin, and vitamin D3 also showed potential preventive effects. Combination therapies, such as flunarizine plus topiramate, valproate plus magnesium, or folic plus pyridoxine, were associated with greater efficacy in migraine prevention compared to monotherapy and with a lower incidence of adverse events. Topiramate, flunarizine, propranolol, valproate, amitriptyline, cinnarizine, and nortriptyline were associated with improvements in quality of life (QoL), but these findings were based on limited evidence. Valsartan and a-dihydroergocryptine were linked to reduced migraine frequency, but these results were largely derived from single studies and require confirmation through larger, high-quality trials.ConclusionThis network meta-analysis confirmed the significant efficacy of topiramate, valproate, and propranolol in migraine prevention and identified potential benefits of memantine, melatonin, vitamin D3, and combination therapies. These findings provide evidence-based treatment options for migraine prevention and suggest promising directions for future research.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42024621316, Identifier: PROSPERO, CRD42024621316.